Selected fruit pomaces: Nutritional profile, health benefits, and applications in functional foods and feeds - Kumar, Harsh; Guleria, Shivani; Kimta, Neetika; Nepovimova, Eugenie; Dhalaria, Rajni; Dhanjal, Daljeet Singh; Sethi, Nidhi; Alomar, Suliman Y; Kuca, Kamil (Current research in food science, 2024)
The utmost objective of every nation is to achieve zero hunger and ensure the health and well-being of its population. However, in impoverished nations, particularly in rural areas, such issues persist on a daily basis. Currently, there is a growing demand for fruit consumption due to their potential health benefits. Surprisingly, their most prevalent by-product is pomace, which is produced in millions of tonnes and is usually discarded as waste after processing or consumption. Even food produced with these kinds of raw resources can contribute to the objective of eradicating world hunger. Owing to these advantages, scientists have begun evaluating the nutritional content of various fruit pomace varieties as well as the chemical composition in different bioactive constituents, which have significant health benefits and can be used to formulate a variety of food products with notable nutraceutical and functional potential. So, the purpose of this review is to understand the existing familiarity of nutritional and phytochemical composition of selected fruit pomaces, those derived from pineapple, orange, grape, apple, and tomato. Furthermore, this article covers pre-clinical and clinical investigations conducted on the selected fruit pomace extracts and/or powder forms and its incorporation into food products and animal feed. Adding fruit pomaces reduces the glycemic index, increases the fibre content and total polyphenolic contents, and reduces the cooking loss, etc. In animal feeds, incorporating fruit pomaces improves the antioxidant enzyme activities, humoral immune system, and growth performance and reduces methane emission.
Keywords: Enrichment; Health; Fruit pomaces; Functional feed; Functional food